Cultural Resilience among Indigenous Community: Exploring the Local Life of Barong Ider Bumi in the Osing Community, Banyuwangi - Arifah, Kiki Ayu; Saputra, Meidi (KnE Social Sciences, 2024)
The Osing Indigenous Community is one of ethnic that exist in Kemiren, Banyuwangi, East Java. They have a unique culture that form local wisdom values. One of these is Barong Ider Bumi. This research aims to explore cultural resilience by investigating the local wisdom contained in the Barong Ider Bumi Tradition. This research was conducted using a qualitative and case study method. All data were collected through interviews, observations, and document analysis. The research shows that Barong Ider Bumi is not only a traditional performance, but also contains deep local wisdom values such as mutual cooperation, helping each other, and belief in God. This tradition reflects the cultural resilience of the Osing people and their close relationship with humans, nature, and ancestral spirits. The research also identified challenges and opportunities in maintaining the continuity of Barong Ider Bumi amidst the dynamics of changing times and modernization. By understanding the values of local wisdom and adhering to traditional policies, it is hoped that the Osing people can maintain and develop their cultural heritage as an integral part of local identity. Overall, this research makes an important contribution to understanding the role of local wisdom in maintaining and strengthening cultural resilience. The implications can be used as a basis for efforts to preserve and develop traditional culture, as well as to provide inspiration to the Osing community and similar groups to maintain and enrich their cultural heritage. Keywords: Barong ider bumi, local wisdom, cultural resilience, osing community